2017
DOI: 10.1111/andr.12345
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of varicocoele and its association with body mass index among 39,559 rural men in eastern China: a population‐based cross‐sectional study

Abstract: Varicocoele is a common cause of male infertility. We undertook a population-based cross-sectional study to evaluate the prevalence of varicocoele among rural men in eastern China and its association with body mass index. A total of 39,559 rural men in six counties in Beijing, Guangdong and Shandong provinces were recruited from 2011 to 2012. The presence and severity of varicocoele were measured by physical examinations. Univariate and multivariate logistic regression models were constructed to assess the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 39 publications
4
31
1
3
Order By: Relevance
“…We excluded twenty-two studies that did not report the outcome of varicocele or did not provide enough data to calculate the ORs. Finally, we identified eleven full-text articles (12, 14, 18, [24][25][26][27][28][29][30][31] that met the inclusion criteria. The search flow chart is shown in Figure-1, and the characteristics of the eleven included articles are summarized in Table-1.…”
Section: Resultsmentioning
confidence: 99%
“…We excluded twenty-two studies that did not report the outcome of varicocele or did not provide enough data to calculate the ORs. Finally, we identified eleven full-text articles (12, 14, 18, [24][25][26][27][28][29][30][31] that met the inclusion criteria. The search flow chart is shown in Figure-1, and the characteristics of the eleven included articles are summarized in Table-1.…”
Section: Resultsmentioning
confidence: 99%
“…A cross‐sectional multicenter study of 7035 young men from six European countries with the median age 19 years showed that the overall prevalence of varicocele was 15.7% (Damsgaard et al ., ). In eastern China, the incidence was 4.83% through the study of 39,559 rural men (Liu et al ., ). And it is a higher incidence of varicocele in the crowd with infertility; a cross‐sectional study showed that the incidence of varicoceles is up to 16.3% in men with fertility requirements who attended an infertility clinic (Dieamant et al ., ), and 26% of infertile men in China suffer from varicocele at present (Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…When the literature is examined, various studies have shown that the incidence of varicocele is decreased in overweight and obese men [29] [30] [31] [32]. In a large-scale study by Liu et al, it was shown that varicocele grade was decreased with reduced body mass index [22] [28]. In our study, while the patients with a low BMI had a low-grade varicocele, the patients with a high BMI had a high-grade varicocele.…”
Section: Discussionmentioning
confidence: 45%
“…The relationship between adolescent varicocele, weight and BMI is still unclear [22]. Although some studies have revealed a positive correlation between the incidence of adolescent varicoceles and weight gain, it has been shown to be inversely proportional to reduced body mass index [23]- [28].…”
Section: Discussionmentioning
confidence: 99%